Indonesian Language Learning Using a Storytelling Approach Based on the History of Dapdap Putih Village - I Made Yogi Putra; I Gede Suwindia; I Nyoman Raka (Universitas Pendidikan Ganesha, 2025)
The lack of interest in reading among students affects their language skills. A lack of varied learning quickly bores students when they follow it. This condition can be overcome by applying a storytelling approach to Indonesian language learning. This study aims to analyze Indonesian language learning using a storytelling approach based on the history of Dapdap Putih village for fifth-grade elementary school students. The type of research used in this study is descriptive qualitative research, with data collection techniques including observation, interviews, and document studies. Data analysis techniques use the Miles and Huberman technique. Data validity testing techniques use triangulation of data sources and triangulation of data collection techniques. The results of this study indicate that Indonesian language learning with a storytelling approach can improve 4 aspects of students' language skills, including reading, listening, writing, and speaking. The storytelling learning model, based on the history of Dapdap Putih Village, is considered effective in increasing students' motivation to learn and improving their language skills. The implication of this study is a strategy to maintain the sustainability of the storytelling learning approach based on the history of Dapdap Putih Village in the future, given that schools involve the younger generation and community leaders in collecting stories.